Needs Analysis of Link and Match on Research Methodology Course: Student-Lecturer Based Teaching and Learning Experiences - Sumarni, Sri; Akhyar, Muhammad; Nizam, Muhammad; Widyastono, Herry; Anggrainingsih, Rini (International Journal of Social Learning (IJSL), 2024)
Research methodology is a mandatory course in higher education. Students are expected to be able to compile research and solve problems according to their field of study. However, many students still have difficulty operationalizing research competency indicators. This research aims to reveal learning needs through the experience of lecturers teaching and students learning in research methodology courses. This research uses an interpretive relativity paradigm with a narrative inquiry approach. Lecturers and students as participants. Data collection techniques using interviews. Data were analyzed using content analysis. By exploring lecturers' teaching experiences and students' learning experiences, information on learning needs is obtained. The learning needs include learning outcomes, literacy technology, learning time, lecturer's teaching experience, obstacles or shortcomings faced by lecturers, and the final learning product. Through the link and match between the learning needs of students and the fulfillment of learning needs from lecturers, a research methodology learning needs analysis is obtained, including learning outcomes, technological literacy, learning time, lecturer teaching experience, obstacles lecturers face, and the final learning product.